SISTEM MONITORING PEGAWAI BERDASARKAN PENUGASAN BERBASIS WEBSITE - Hanural, Tabia; Pramudwiatmoko, Arif (Infotech: Journal of Technology Information, 2024)
The Cepu Oil and Gas Human Resources Development Center faces challenges in the efficiency of reporting and monitoring employee assignments due to the use of conventional methods that are prone to delays and inaccuracies in data. The impact of the absence of a web-based performance appraisal application causes obstacles in managerial decision making, decreased productivity, and increased occupational safety risks. To overcome this problem, a web-based employee performance appraisal system was developed using XAMPP, Laravel, HTML, PHP, CSS, and MySQL technologies, by applying the Waterfall Model system development method. The development process includes designing, implementing, and testing key features such as employee data input, assignments, reports, and performance appraisals by supervisors. The approach used includes quantitative analysis through questionnaires and qualitative analysis through interviews. The results show that this application has succeeded in increasing the efficiency and accuracy of reporting, enabling real-time access to data, and supporting faster and more precise decision making at the Cepu Oil and Gas Human Resources Development Center. ABSTRAKPusat Pengembangan Sumber Daya Manusia Migas Cepu menghadapi tantangan dalam efisiensi pelaporan dan monitoring penugasan pegawai akibat penggunaan metode konvensional yang rentan terhadap keterlambatan dan ketidakakuratan data. Dampak dari ketiadaan aplikasi penilaian kinerja berbasis web menyebabkan hambatan dalam pengambilan keputusan manajerial, penurunan produktivitas, dan peningkatan risiko keselamatan kerja. Untuk mengatasi masalah ini, dikembangkan sebuah sistem penilaian kinerja pegawai berbasis web menggunakan teknologi XAMPP, Laravel, HTML, PHP, CSS, dan MySQL, dengan menerapkan metode pengembangan sistem Model Waterfall. Proses pengembangan meliputi perancangan, implementasi, serta pengujian fitur-fitur utama seperti input data pegawai, penugasan, laporan, dan penilaian kinerja oleh supervisor. Pendekatan yang digunakan mencakup analisis kuantitatif melalui kuesioner dan kualitatif melalui wawancara. Hasil menunjukkan bahwa aplikasi ini berhasil meningkatkan efisiensi dan akurasi pelaporan, memungkinkan akses real-time terhadap data, dan mendukung pengambilan keputusan yang lebih cepat dan tepat di PPSDM Migas Cepu.